ChemInform Abstract: Precursor Routes to Complex Ternary Intermetallics: Single‐Crystal and Microcrystalline Preparation of Clathrate‐I Na8Al8Si38 from NaSi + NaAlSi. Issue 32 (August 2015) - Dong, Yongkwan; Chai, Ping; Beekman, Matt; Zeng, Xiaoyu; Tritt, Terry M.; Nolas, George S.
Abstract Microcrystalline clathrate‐I compounds Na8AlxSi46‐x (x = 4, 6, 8) are synthesized by spark plasma sintering using a NaSi/NaAlSi mixture as precursor (973 K, 3 h).